Ground Beetle (Coleoptera : carabidae) occurrence in three forest types in Sarawak - Lau, Eng (Universiti Malaysia Sarawak (UNIMAS), 2009)
The occurrence and diversity of ground beetles was studied in a peat swamp forest (PSF), lowland forest (LF) and kerangas forest (KF), Sarawak. Three methods used in this study were pitfall trap, Malaise trap and modified Pennsylvania light trap. The sampling period for the study was 10 days. A total number of 302 carabids belonging to 47 species were collected. 300 individuals were collected by modified Pennsylvania light trap~ Pitfall traps and Malaise traps are obviously not a suitable method for catching carabids in such habitats. 84 ground beetles were collected from PSF (H'=3.992), 93 individuals from LF (H'=3.842) and 123 carabids from KF (H'=4.184). Species compositions and the dominant species were different among the three forests: only II species were found at all forest types, while 5 species were unique to PSF, 7 species unique to LF and 12 species unique to KF. 32% of the species were singletons and the cumulative species curves for the three forests do not reach an asymptote. It is concluded that forest conditions and the level of disturbance affects the occurrence ofthe ground beetles.